The effect of various counter plate methods on creasing quality in carton packaging production - (:unkn) unknown (My University, 2009)
Bu çalışmada üretimde en çok kullanılan karşı kalıp yöntemleri (hazır karşı kalıp ve hazır oluk yöntemleri) kesim adedine bağlı olarak piliyaj kalitesi ve maliyet açısından karşılaştırılmıştır. Kesim işlemi maşalı tipo baskı makinesinde yapılmıştır. 450 gr/m2 gramajda, 0,6mm kalınlığında karton kullanılarak kartonun su yönüne dik ve paralel olarak planlanan piliyajlar için aynı karşı kalıp ölçüleri (0,6mm x 1,5mm) kullanılmıştır. Karşı kalıpların piliyaj performansı 100.000 adet kesim yapılarak test edilmiş ve kartonun piliyaj ölçümü su yönüne paralel ve dik olarak, her 5000 adette bir alınan örnekler üzerinde BS6965 esasına uygun olarak “Pira Crease and Board Stifness tester” cihazında yapılmıştır. Yapılan test baskıları sonucunda kartonun su yönüne dik olan piliyajlar kartonun su yönüne paralel olan pilyajlara göre daha kararlı, su yönüne paralel olan piliyajlarda hazır oluk yöntemi ile yapılan piliyajlar hazır karşı kalıp yöntemi ile yapılan piliyajlara göre daha kararsız bulunmuştur. Hazır karşıkalıp yöntemi en pahalı, hazır oluk yöntemi ise buna göre daha ucuz görünürken, en fazla hazırlık zamanı gerektiren yöntem hazıroluk yöntemi en kısa hazırlık zamanı gerektiren yöntem ise hazır karşı kalıp yöntemi çıkmıştır.

In this study, the most used counter plate methods (ready counter plate (rillma) and crease channel) in production, based on the number of cuts, have been compared in terms of the quality of creasing. The cutting procedure is performed using a Heidelberg platen press and cardboard with a weight and thickness of 450 gr/$m^ 2$ and 0.6mm respectively. The creasing method is planned to be parallel and vertical to the direction of the carton fibre. Creasing measurements are used with the same measurements of 0.6 x 1.5mm for the creasing that are vertical and parallel to the direction of the cardboard fibre. Creasing performance of counter plates are tested after 100.000 cuts and measurements of the cardboard creasing, upon samples from every 5000 and by conforming to the BS6965 principle, are done in the “Pira Crease and Board Stiffness tester” device. As a result of the test prints, the crease vertical to the direction of the cardboard fibre have been found to be more stable compared to those parallel to the cardboard fibre, while the crease channel of the crease parallel to the fibre have been found to be more unstable compared to crease made by the ready counter plate (Rillma) method. Preparation stage: found in the longest crease channel method and the shortest counterplate (Rillma) method. As a result, the rilma method can be preferred for high circulation orders and the crease channel method can be preferred for low circulation orders.
Karton ambalaj üretiminde çeşitli karşı kalıp yöntemlerinin piliyaj kalitesine etkisi